From Chief Editor's desk / Irina Mohd Akhir - Mohd Akhir, Irina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
It is my pleasure to present the latest edition of the FPHP Bulletins Series 2. This publication is the result of a collaborative effort by our dedicated team & talented contributors, whose hard work has brought together a rich variety of articles showcasing the vibrant life & activities of our faculty. Proud to feature 22 selected articles in both Bahasa Malaysia & English. This volume carries the theme "Colors of Hospitality: Faculty Happenings 2024," capturing a richer understanding of FPHP dynamic environment.